Landscape-history of grasslands surround the Naszály and the examination of their natural status - Fehér, Zsófia (JOURNAL OF LANDSCAPE ECOLOGY, 2015)
Change in the regional land use, the fragmentation of areas cause changes in composition of species at our grasslands, result in a reduction in the diversity and endanger the viable populations. During the grassland planning it is important to know the landscape history of grasslands and need to examine what characterizes their store of species and their structure in their actual condition. With this survey, I aim to assess the nature protection values and the structure of the grasslands around the hill „Naszály”, to contribute to enhance the landscape protection management of the region by revealing the role of the landscape heritage and the natural environmental impacts, and to draw the attention to the tendencies that are important in respect of the nature and landscape protection. I have demonstrated by analysis of the landscape-history, that while at the northern hill foot grasslands remained unchanged in the last more than 200 years and are up to now protected, at the areas of southern hill foot the cultivation branches change constantly and up to now the grasslands have fragmented and their subsistence is endangered. The coenological samplings data of southern and northern hill foot areas – which were studied by ecological parameters and clasteranalysis – have confirmed that in the store of species in the southern area is experienced running down, the anthropogenic disturbance is more pronounced in their structure then in the northern area. At the southern side of Naszály the grasslands, which are situated on area of mine or are wanted to plant with trees, aren’t protected, their survival and the maintenance of their biodiversity isn’t provided, therefore it is need to increase the efficiency of the conservation management at the southern hill foot by the protection of new areas.
Keywords: land use; biodiversity; conservation